Penelitian ketahanan polybag wadah bibit tanaman ditinjau dari sifat ketahanan sobek - Supraptiningsih Supraptiningsih; Arum Yuniari; Irene Sri Sukaeni (Majalah Kulit, Karet, dan Plastik, 1995)
The aim of this research is to know quality of polybag considered of tear strength. Research applies 135 polibags. 27 for blanks and 108 for seed planted. These are 3 variations in this research, they are thickness of polybag variation (0,03 mm; 0,05 mm and 0,01 mm), time plants variation (3; 45 ; 6 month) and